Role of anisotropy for protein-protein encounter - Schluttig, Jakob; Korn, Christian B.; Schwarz, Ulrich S. (Arxiv, 2010)
Protein-protein interactions comprise both transport and reaction steps. During the transport step, anisotropy of proteins and their complexes is important both for hydrodynamic diffusion and accessibility of the binding site. Using a Brownian dynamics approach and extensive computer simulations, we quantify the effect of anisotropy on the encounter rate of ellipsoidal particles covered with spherical encounter patches. We show that the encounter rate $k$ depends on the aspect ratios $ξ$ mainly through steric effects, while anisotropic diffusion has only a little effect. Calculating analytically the crossover times from anisotropic to isotropic diffusion in three dimensions, we find that they are much smaller than typical protein encounter times, in agreement with our numerical results.